THE EFFECT OF MULTIPLE REPRESENTATION METHOD ON STUDENTS' REASONING SKILL IN LEARNING RESPIRATORY SYSTEM - Alin Rizki Pratami, - (2018)
This study aims to analyze the effect of multiple representation method on students' reasoning skill. The method was designed to present the information of respiratory system topic in more than one representation, and also to lead students to translate the information into different type of representation in order to helps them constructing their own understanding. The type of representation used in this study were text, picture, video, table, graph, chemical formula, and hands on activity. The result of students' learning process was measured using instrument to obtain students' reasoning skill. The reasoning skill is expressed in argument analyzed using Toulmin's Argument Pattern (TAP). The analysis of reasoning skill was divided based on the score of components of argument, level of argument, and quality of argument. This study used pre-experiment method (n=21) with one group pre and posttest design. The result showed that the multiple representation method helped the students to improve their reasoning skill indicated by the positive N-gain for the completeness of argument component (N-gain=0.30). The improvement in level of arguments is shown from pretest and posttest, the arguments in pretest were on level 1 and level 2, while the arguments in posttest shows the decreasing percentage on level 1, increasing percentage on level 2, and some of arguments reached level 3. Meanwhile, the quality of argument shifted from the domination of weak arguments to domination of strong arguments. ;---Peneltian in bertujuan untuk menganalisis pengaruh metode multi representasi terhadap keterampilan bernalar siswa. Metode yang dirancang sedemikian rupa agar dapat menyajikan informasi dari topik sistem pernafasan dengan lebih dari satu representasi, dan mengarahkan siswa untuk menafsirkan informasi ke dalam representasi yang berbeda pula untuk membantu mereka membangun pemahamannya. Jenis representasi yang digunakan dalam penelitian ini adalah teks, gambar, video, tabel, grafik, dan rumus kimia. Hasil dari proses belajar siswa kemudian diukur untuk mendapatkan hasil kemampuan bernalar siswa. Jenis representasi yang digunakan adalah teks, gambar, video, tabel, grafik, rumus kimia, dan kegiatan hands-on. Hasil dari pembelajaran siswa diukur menggunakan instrumen untuk kemampuan bernalar. Kemampuan bernalar terekspresikan dalam argumen yang dianalisis menggunakan pola argumen Toulmin (Toulmin's Argument Pattern). Analisis kemampuan bernalar dibagi berdasarkan kekomplitan komponen argumen, level argumen, dan kualitas argumen. Penelitian ini menggunakan metode pra-penelitian (n=21) dengan rancangan satu kelompok prates dan postes. Hasil dari penelitian menunjukan bahwa metode multi representasi membantu siswa meningkatkan kemampuan bernalar mereka, terindikasi dari positif N-gain untuk kekomplitan komponen argumen (N-gain=30). Peningkatan level argumen terlihat dari prates dan postes, argumen dalam prates berada pada level 1 dan level 2, sedangkan hasil postes menunjukan penurunan persentasi argumen pada level 1, peningkatan persentasi argumen pada tingkat 2, dan beberapa argumen mencapai level 3. Sementara itu hasil kualitas argumen menunjukan peralihan dominansi dari argumen yan lemah ke argumen yang kuat.